2002
DOI: 10.1148/radiol.2222010669
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptance of CT Colonography and Conventional Colonoscopy: Prospective Comparative Study in Patients with or Suspected of Having Colorectal Disease

Abstract: CT colonography was considered less painful and less difficult overall than colonoscopy and was the preferred examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(98 citation statements)
references
References 20 publications
3
86
0
8
Order By: Relevance
“…Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9]. Moreover, patients generally prefer CTC instead of barium enema examination or colonoscopy [10][11][12][13]. However, concerns were raised about recommending CTC as routine screening tool because of potential harm [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9]. Moreover, patients generally prefer CTC instead of barium enema examination or colonoscopy [10][11][12][13]. However, concerns were raised about recommending CTC as routine screening tool because of potential harm [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that noninvasive methods such as CT virtual colonoscopy [15], MR cholangiopancreatography [16], and MR angiography of the carotid arteries [17] are more widely accepted by patients than the traditional invasive approaches [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the success of a method is undeniably associated with the intrinsic acceptance of the method by the patients, who are increasingly pursuing noninvasive and outpatient diagnostic examinations [14]. On the one hand, recent studies have shown that noninvasive tools such as CT virtual colonoscopy [15], magnetic resonance (MR) cholangiopancreatography [16], and MR angiography of the carotid arteries [17] are widely accepted by patients more than the traditional invasive approach, on the other hand it is known that conventional coronary angiography (CCA) may cause intense concern and anxiety in the patients and affect their quality of life especially in the hours before the examination, with the need for pharmacological and/or psychological treatment [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been reports about a possible correlation between nephrogenic fibrosing dermopathy (NFD) and the intravenous administration of gadolinium compounds (20). As far as patient acceptance is concerned, several trials revealed a higher acceptance rate for virtual colonography compared to optical endoscopy (21)(22)(23). The need to undergo bowel cleansing yet is rated as the most unpleasant part of the virtual colonography exam (21-25) and patient discomfort scores can be significantly improved with tagging preparations previously shown for CT colonoscopy (CTC) (26).…”
Section: Discussionmentioning
confidence: 99%